Predictive model of the psychological well-being of nursing students during the COVID-19 lockdown - Lourenço, Tânia Marlene Gonçalves (2022)
Introduction: Lockdowns due to the COVID-19 pandemic radically changed nursing education. Along with social isolation, the transition to distance education affected the well-being of students in several countries, particularly Portugal and Spain. Objectives: To identify which variables are predictors of psychological well-being for Portuguese and Spanish nursing students during mandatory lockdowns. Methods: A multicenter, cross-sectional, descriptive, correlational study involving a sample of 1075 students (944 women, mean age 22.46 + /−4.95 years). Data were collected from an online questionnaire which applied the following scales: Perceived Stress Scale (α =.820); Brief COPE-14 Subscales (α =.430 < 0.930); Well-being Manifestations Measure Scale (α =.940); Herth Hope Index (α =.850). A multiple regression model was created to predict the psychological well-being of nursing students. Results: The following predictor variables were identified in the model of the psychological well-being of students during the COVID-19 pandemic: perceived stress (β =.405; p ≤.001); hope (β =.404; p ≤.001); and the mechanisms of active coping (β =.405; p ≤.001), planning (β =.097; p ≤.001), and positive reinterpretation (β =.053; p =.12). These five variables predicted 62.0% of the nursing students’ psychological well-being (R2 =.620; F = 350.82; p ≤.001). Conclusion: Promoting students’ mental health is essential, especially in periods of great adversity, such as a pandemic. Our results lead the way for the design and validation of an intervention program that addresses the five variables identified as predictors of students’ psychological well-being.